2018
DOI: 10.2967/jnumed.118.215715
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience of Rechallenge 177Lu-PSMA Radioligand Therapy After an Initial Good Response in Patients with Advanced Prostate Cancer

Abstract: Our aim was to retrospectively evaluate the feasibility of rechallenge 177 Lu-prostate-specific membrane antigen ( 177 Lu-PSMA) radioligand therapy. Methods: Rechallenge radioligand therapy was defined as subsequent treatment with 177 Lu-PSMA after initial exposure with an excellent response followed by progression. Biochemical, radiographic, clinical antitumor response, and adverse events were analyzed. Prostate-specific antigen (PSA) progression-free survival (PFS) and overall survival were calculated. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…Yordanova et al [16] recently reported a clinical benefit in 30 177 Lu-PSMA-617 re-treated patients with a median OS of 25 months versus 9 months in patients who received only one 177 Lu-PSMA-617 treatment period, each period consisting of several treatment cycles. Similar beneficial results were reported for 177 Lu-PSMA-I&T re-treatment by Grubmüller et al [17] and Gafita et al [18]. Basically, these retrospective analyses raise the question whether higher activities than 6 GBq of 177 Lu-PSMA-617 would fit more appropriate as Grade 4 toxicity is rare, even in rechallenged patients, with reasonable efficacy.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Yordanova et al [16] recently reported a clinical benefit in 30 177 Lu-PSMA-617 re-treated patients with a median OS of 25 months versus 9 months in patients who received only one 177 Lu-PSMA-617 treatment period, each period consisting of several treatment cycles. Similar beneficial results were reported for 177 Lu-PSMA-I&T re-treatment by Grubmüller et al [17] and Gafita et al [18]. Basically, these retrospective analyses raise the question whether higher activities than 6 GBq of 177 Lu-PSMA-617 would fit more appropriate as Grade 4 toxicity is rare, even in rechallenged patients, with reasonable efficacy.…”
Section: Discussionsupporting
confidence: 76%
“…The currently most commonly used Reponse Evaluation Criteria In Solid Turmors (RECIST) [2] are based on cross-sectional abdominopelvic imaging together with bone scintigraphy and PSA serum levels. 68 Ga-PSMA-11 PET/CT revealed a higher probability for a positive PET-finding in patients with low PSA values (≤ 0.5 ng/ml) than any other imaging modality including 18 F-choline PET/CT [3], which can substantially influence the clinical management. In fact, 68 Ga-PSMA-11 provides more accurate assessment than conventional imaging [4] and can also be superior to 18 F-sodium fluoride PET/CT for the evaluation of bone metastases in response to 223 Ra-chloride therapy [5].…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, these findings bear a resemblance to the genetic changes reported in glucocorticoid receptor-driven enzalutamide resistance (8). While the underlying radiobiological mechanisms instigating PSMA down-regulation during treatment and in recurrent tumors could be different, these observations could potentially explain the reduced treatment efficacy noted upon repeated PSMA-targeted RIT and radioligant therapy (5,35,36). Although preclinical models have limitations, the present outcome demonstrates efficacy of serial [ 225 Ac]hu11B6 treatment in a mouse model; relapsing tumors in mice express abundant levels of hK2 (KLK2) (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, a repeated course of [ 177 Lu]Lu-PSMA RLT is being administered to some patients with a prior excellent response [44,45] and authors are investigating the prognostic factors [29]. They showed that rechallenge therapy is safe.…”
Section: Psa Declinementioning
confidence: 99%